Evaluation of forestry models for future settlement of forestry plantations under land claims : the case of Jessievale and Roburna forest plantations in Mpumalanga, South Africa - Chirwa, Paxie W. (University of Pretoria, 2014)
Dissertation (MSc)--University of Pretoria, 2013.